Construct validity and internal consistency of a Malay version of the FAMCARE scale for measures of informal caregivers satisfaction - Rafi Mahmoud Alnjadat; Wan Aasim Wan Adnan; Zalina Ismail (Universiti Kebangsaan Malaysia, 2014)
Evaluating the satisfaction of caregivers is a highly subjective procedure and there is a need for a culturally appropriate, validated and sufficiently tested measurement tool to identify their needs in a clinical setting in order to improve the quality of care. FAMCARE is a self-report scale assessing patient/ caregivers’ satisfaction with outpatient care. This study evaluated the validity and internal consistency of a Malay-language version of the FAMCARE scale amongst Malaysian informal caregivers. A total of 45 Malaysian informal caregivers in the outpatient oncology clinic, Hospital Universiti Sains Malaysia completed the questionnaire. Responses were checked for construct validity (including exploratory factor analysis to check the factor structure of the scale) and internal reliability. The 20 items of the FAMCARE scale were subjected to principal axis factoring (PAF) using SPSS, starting with assessing suitability of the data for factor analysis. Correlation matrix showed the presence of many coefficients of 0.3 and above. The Kaiser–Mayer-Olkin value was 0.79 and the Barlett’s Test of sphericity was highly significant (p<.001). PAF showed the presence of four components with eigenvalues exceeding 1, explaining 60.8% of the cumulative variance. The items were loaded in four domains with satisfactory inter-factor correlations. The general FAMCARE questionnaire as a whole was found to have high internal reliability (Cronbach’s α = 0.93). The Malay-language version of the FAMCARE scale appeared as a valid and reliable tool for assessing informal caregiver’s satisfaction in outpatient settings, although it would be preferable to eliminate weak items which have low factor loading.